Carbon material for catalyst support of polymer electrolyte fuel cell and method for producing same
The development of a carbon material with a three-dimensionally branched dendritic structure, optimized through specific manufacturing steps, addresses the issue of bulk carbon in catalyst supports for solid polymer fuel cells, resulting in improved oxygen gas diffusion, water discharge, and high current characteristics.
Patent Information
- Application Number
- JP2021060954
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-03-31
AI Technical Summary
Existing carbon materials for catalyst supports in solid polymer fuel cells contain bulk carbon that cannot be fully eliminated by conventional classification treatments, leading to reduced oxygen gas diffusion and water discharge performance, which hinders the achievement of optimal high current characteristics.
A carbon material with a three-dimensionally branched dendritic structure is developed, characterized by a specific particle size distribution and pore size optimization. This is achieved through a manufacturing process involving silver acetylide decomposition, heat treatment, grinding, and activation with carbon dioxide to minimize bulk carbon and enhance porosity.
The optimized carbon material significantly improves oxygen gas diffusion and water discharge performance, leading to enhanced high current characteristics and durability of the fuel cell, while minimizing bulk carbon content.
Smart Images

Figure 0007655761000002 
Figure 0007655761000003 
Figure 0007655761000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a carbon material for a catalyst support of a polymer electrolyte fuel cell and a method for producing the same. [Background technology]
[0002] In recent years, polymer electrolyte fuel cells that can operate at low temperatures of 100° C. or less have attracted attention, and are being developed and put to practical use as vehicle driving power sources and stationary power generation devices. A typical polymer electrolyte fuel cell has a basic structure (unit cell) consisting of a membrane electrode assembly (MEA) in which a proton-conductive electrolyte membrane is sandwiched between two catalyst layers serving as an anode and a cathode, respectively, on both outer sides of the membrane electrode assembly, gas diffusion layers that are placed on the outer sides of the catalyst layers on both sides of the membrane electrode assembly, and separators that are further placed on the outer sides of these gas diffusion layers, and is usually constructed by stacking the number of unit cells required to achieve the required output.
[0003] In such a unit cell of a polymer electrolyte fuel cell, an oxidizing gas such as oxygen or air is supplied to the cathode side, and a fuel such as hydrogen is supplied to the anode side from the gas flow paths of the separators arranged on the anode and cathode sides, respectively. The oxidizing gas and fuel (sometimes called "reactant gases") are then supplied to the catalyst layer via the gas diffusion layers, and work is extracted by utilizing the energy difference (potential difference) between the chemical reaction occurring in the anode catalyst layer and the chemical reaction occurring in the cathode catalyst layer. For example, when hydrogen gas is used as the fuel and oxygen gas is used as the oxidizing gas, the chemical reaction occurring in the anode catalyst layer [oxidation reaction: H 2 →2H + +2e - (E 0 =0V)] and the chemical reaction occurring in the cathode catalyst layer [reduction reaction: O 2 +4H + +4e - →2H 2 O(E 0=1.23V) is extracted as work.
[0004] Here, as for the catalyst that forms the above-mentioned catalytic layer and causes a chemical reaction, a porous carbon material is usually used as the catalyst carrier from the viewpoints of electronic conductivity, chemical stability, and electrochemical stability, and as the catalytic metal, Pt or a Pt alloy that can be used in a strongly acidic environment and shows high reaction activity for both oxidation and reduction reactions is mainly used. As for the catalytic metal, since the above-mentioned oxidation and reduction reactions generally occur on the catalytic metal, in order to increase the utilization rate of this catalytic metal, it is necessary to increase the specific surface area per mass, and particles of about several nm in size are usually used.
[0005] The catalyst support for supporting such catalytic metal particles needs to be a porous carbon material with a large specific surface area in order to increase the supporting ability as a support, i.e., to increase the number of sites for adsorbing and supporting the catalytic metal particles of about several nm. At the same time, the catalyst support is required to have a large mesopore volume, i.e., a large volume of mesopores with a pore diameter of 2 to 50 nm, so that the catalytic metal particles can be supported in as highly dispersed a state as possible. At the same time, when the catalytic layers that serve as the anode and cathode are formed, it is necessary to form fine pores in the catalytic layer that are suitable for diffusing the reactive gas and discharging the generated water, so that the reactive gas supplied to the catalytic layer can be diffused without resistance and the water generated in the catalytic layer (generated water) can be discharged without delay.
[0006] In order to achieve such a purpose, porous carbon materials have been proposed that have a relatively large specific surface area and mesopore volume, and at the same time, have a dendritic structure with three-dimensionally developed branches, and in particular, dendritic carbon nanostructures that are produced using a metal acetylide such as silver acetylide having a three-dimensionally branched dendritic structure as an intermediate and that maintain the three-dimensional dendritic structure have attracted attention (see, for example, Patent Documents 1 to 4). All of the carbon materials for catalyst supports described in Patent Documents 1 to 4 have a relatively large specific surface area and mesopore volume, and are also excellent in durability, and therefore have excellent large current characteristics that are important for extracting large output, particularly when used as a fuel cell for an automobile. For the catalyst support carbon material produced by such a procedure, when it is actually used in a catalyst layer, it is required that the particle size is from 20 nm to about 1 μm at most. It is said that within such a range, even if the catalyst support carbon material has a relatively large specific surface area or mesopore volume, the mechanical strength is maintained, and the thickness of the catalyst layer can be controlled within an appropriate range. In order to obtain a catalyst support carbon material having a particle size of about 1 μm at most, it is usually crushed, pulverized, and classified (hereinafter, these will be collectively referred to as "classification") using a device such as a jet mill before using it for the production of the next catalyst layer, so as to remove relatively large particles exceeding 1 μm.
[0007] According to the investigations conducted by the inventors of the present application to date, it has been found that even when the above-mentioned classification process is performed, coarse, highly crystalline, and non-porous carbon aggregates that are too large to be removed are mixed in (remain) and that such carbon aggregates are derived from "carbon (soot) with low aromaticity" resulting from the manufacturing process of carbon materials for catalyst supports. Based on this assumption, the inventors have devised various manufacturing process measures, such as optimizing the amount of acetylene gas injected in the manufacturing process (see Patent Document 5) or adding a treatment with a specified oxidizing agent solution in the manufacturing process (see Patent Document 6), thereby proposing to suppress the above-mentioned carbon aggregates that are mixed in (remain) in carbon materials for catalysts. However, when the inventors of the present application further investigated the lump carbon that was not removed by the above-mentioned classification treatment, they found that such lump carbon was a particle smaller than that removed by the classification treatment, and was agglomerated with low aromatic carbon (soot) and skeletal carbon of the carbon material for catalyst carrier, which were strongly connected, but had many voids and were light (small mass), and the method described in Patent Document 5 as above could not completely suppress the generation of lump carbon due to the influence of a slight excess of acetylene gas injection, and the method described in Patent Document 6 had the problem that the process was complicated and the target carbon material was partially oxidized and removed, reducing the yield. Moreover, it was found that simply classifying such lump carbon that was not removed did not work because it had many voids and was light.
[0008] Incidentally, the carbon material for catalyst carrier made of a dendritic carbon nanostructure having a three-dimensional dendritic structure that has been studied so far is a porous carbon having a high specific surface area, and is known to have excellent relatively high current characteristics as a catalyst for fuel cells [output voltage at a high current, particularly high current (high load) characteristics that are important for drawing out a large output when used as a fuel cell for an automobile], and the inventors of the present application are also studying further improvement of such high current characteristics. For example, as described in Patent Document 7, efforts have been made to provide a predetermined oxidation treatment process in the manufacturing process in order to reduce the above-mentioned "low aromatic carbon (soot)" and the clumped carbon generated thereby, or as described in Patent Document 8, efforts have been made to adjust the silver nitrate concentration and reaction temperature in the manufacturing process by focusing on optimizing the number of branches and branch diameter of the three-dimensional dendritic structure. However, although the method described in Patent Document 7 can selectively remove "low aromatic carbon (soot)", it is limited to the vicinity of silver particles that have an oxidation catalytic action, and therefore the effect of reducing clumped carbon is also limited. Furthermore, the method described in Patent Document 8 does not mention the particle size of the carbon material described later in the present invention, and is insufficient for realizing optimal interparticle voids. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] WO 2014 / 129597 [Patent Document 2] WO 2015 / 088025 [Patent Document 3] WO 2015 / 141810 [Patent Document 4] WO 2016 / 133132 [Patent Document 5] WO 2018 / 182045 [Patent Document 6] WO 2020 / 066010 [Patent Document 7] WO 2018 / 182048 [Patent Document 8] WO 2018 / 182047 Summary of the Invention [Problem to be solved by the invention]
[0010] The large current characteristics as described above are usually greatly affected by the oxygen gas diffusion in the catalyst layer and the discharge performance of the generated water, so it is assumed that the particle size of the carbon material to be the catalyst support and the pores in the catalyst layer, especially the macropore size, must be optimized. In fact, the optimal particle size conditions for the carbon material for the catalyst support with a three-dimensional dendritic structure have not been known so far, so there was concern that the inherent large current characteristics could not be brought out. In other words, it is assumed that the oxygen gas diffusion and discharge of the generated water are carried out through the surface of the carbon material for the catalyst support → the inter-branch voids and inter-particle voids, but if a large amount of the above-mentioned unremoved clumped carbon is contained, the surface of the dendritic carbon nanostructure exposed to the void surface is reduced, which is thought to hinder the oxygen gas diffusion. In addition, it is also thought that the large voids derived from such clumped carbon cause the flow of oxygen gas and water vapor to pass through a short path, preventing the oxygen gas diffusion in the catalyst layer from being effectively carried out.
[0011] Therefore, it was thought that reducing as much as possible the lump carbon that could not be removed even by conventional classification treatment would make it possible to restore the macropore size in the resulting carbon material for catalyst support and in the catalyst layer using the same to its original appropriate state, and that this would improve the performance of oxygen gas diffusion and discharge of generated water, thereby improving the large current characteristics.
[0012] Therefore, the inventors of the present application have worked diligently to determine how to reduce such clumped carbon that cannot be removed by conventional classification processes and how to specify the properties of the carbon material for catalyst carriers obtained thereby, and have obtained the following findings. In other words, the idea was reached that the first crushing and classification process would remove coarse carbon clumps while exposing the carbon with low aromaticity present inside the powder to the surface, and that subsequent contact with a relatively high-temperature gas, particularly carbon dioxide gas, would enable the carbon with low aromaticity to be selectively and evenly consumed, and further that, once the mechanical strength of the clumped carbon containing it had decreased, it would be possible to remove as much of it as possible by subsequent crushing and classification processes.
[0013] Then, in the desired carbon material for catalyst carrier obtained by carrying out the first crushing and classification process based on the above-mentioned idea, contact with carbon dioxide (activation), and subsequent further crushing process, the problematic lump carbon is eliminated as much as possible, and as a result, the proportion of particle sizes of 1 μm or less will be reduced, and this can be determined by a laser diffraction scattering measurement method suitable for this particle size range, and it has been found that the macropores are not only large, but also have an optimal size for diffusing oxygen gas and discharging generated water, and that this can be expressed by a mode diameter that appears in the pore diameter range of 20 nm to 200 nm measured by mercury porosimetry, which is suitable for accurately measuring material voids of macropore size, and that these actually correlate well with evaluations of large current characteristics and durability. Among the ideas of the inventors of the present application, the activation treatment using carbon dioxide is partially used in, for example, Patent Document 4, but such conventional activation treatments are intended to make the porous carbon more porous, increase the specific surface area, or increase the number of micropores, and have not foreseen the selective consumption of the lump carbon that is the object of removal in this invention, or the contribution to high current characteristics and durability by optimizing the particle size in combination with the subsequent crushing treatment.
[0014] The present invention has been made based on the above-mentioned findings, and an object of the present invention is to provide a carbon material for a catalyst support suitable for producing a catalyst for a polymer electrolyte fuel cell, which can eliminate as much of the agglomerated carbon as possible, in particular optimize the size of the macropores, and further has excellent high current characteristics and durability required for use as a fuel cell. Another object of the present invention is to provide a method for defining such a carbon material for a catalyst support from the proportion of particle sizes of 1 μm or less and the mode diameter appearing in the pore diameter range of 20 nm to 200 nm measured by mercury porosimetry. Furthermore, another object of the present invention is to provide a method for producing such a carbon material for a catalyst support. [Means for solving the problem]
[0015] That is, the gist of the present invention is as follows. [1] A carbon material for a catalyst support used for a catalyst support of a polymer electrolyte fuel cell, the carbon material having a three-dimensionally branched dendritic structure, characterized in that the carbon material for a catalyst support simultaneously satisfies the following (1) and (2): (1) In particle size distribution measurement using a laser diffraction / scattering particle size analyzer, the cumulative distribution [%] of particles with a particle diameter of 1 μm or less based on volume diameter is DL, and the cumulative distribution [%] of particles with a particle diameter of more than 1 μm is DH, and the DL / DH ratio is 1.5 or more. (2) The mode diameter in the pore diameter range of 20 nm to 200 nm measured by mercury porosimetry is 40 nm to 70 nm. [2] Cumulative pore volume V of pores with diameters of 5 to 20 nm determined by analysis of nitrogen gas adsorption isotherms using the Dollimore-Heal method 5-20 The carbon material for a catalyst support according to [1], wherein the viscosity is 0.17 to 0.50 mL / g. [3] In the nitrogen gas adsorption isotherm, the amount of nitrogen gas adsorbed at a relative pressure of 0.95 to 0.99 V macro The carbon material for a catalyst support according to [1] or [2], characterized in that the molecular weight is 500 to 1600 cc(STP) / g. [4] The BET specific surface area determined by BET analysis of nitrogen gas adsorption isotherm is 400 to 1500 m 2 / g. [5] Raman spectroscopy 1550-1650cm -1 The half-width ΔG of the G-band detected in the range of 50-70 cm -1 The carbon material for a catalyst support according to any one of [1] to [4], [6] The above V 5-20 The carbon material for a catalyst support according to any one of [2] to [5], wherein the molecular weight of the carbon material is 0.17 to 0.40 mL / g. [7] A method for producing a carbon material for a catalyst support of a polymer electrolyte fuel cell, comprising the steps of: The method includes a step of removing silver from a composite material containing silver and carbon obtained by decomposing silver acetylide, and then performing a heat treatment at a temperature of 1400° C. or more and 2300° C. or less in a vacuum or in an inert gas atmosphere to obtain a carbon material intermediate, The method for producing a carbon material for a catalyst support of a polymer electrolyte fuel cell comprises a first pulverization step of pulverizing the carbon material intermediate, an activation step of activating the pulverized carbon material by contacting it with carbon dioxide, and a second pulverization step of pulverizing the activated carbon material. Effect of the Invention
[0016] According to the carbon material for a catalyst support of the present invention, it is possible to provide a carbon material for a catalyst support suitable for producing a catalyst for a polymer electrolyte fuel cell, which can eliminate clumped carbon as much as possible, in particular optimize macropores, as described above, and further has excellent large current characteristics and durability required for use as a fuel cell. Moreover, according to the production method of the present invention, a method for producing such a carbon material for a catalyst support can be provided. [Brief description of the drawings]
[0017] [Figure 1] 1 shows the particle size distribution (frequency distribution; upper diagram) and cumulative distribution (lower diagram) measured by a laser diffraction / scattering type particle size distribution analyzer for the carbon material for catalyst carriers of Example 1 described later. In the cumulative distribution in the lower diagram, the part indicated by the dashed line is a particle diameter of 1 μm and a cumulative distribution of 79.4%. [Diagram 2] FIG. 2 shows the particle size distribution (frequency distribution; upper graph) and cumulative distribution (lower graph) measured by a laser diffraction / scattering particle size distribution analyzer in Comparative Example 1 described later. [Diagram 3] FIG. 3 is a graph showing the mode diameter of pores in the range of 20 nm to 200 nm measured by mercury porosimetry for each of the carbon materials for catalyst supports in Example 1, Example 2, Comparative Example 1, Comparative Example 6, and Comparative Example 10 described below. [Figure 4] 4 is an explanatory diagram (photograph) showing the structure (voids, aggregates) confirmed by SEM observation of the carbon material for a catalyst carrier of Example 1 described later. The area surrounded by a white dashed line in the figure shows an example of a small void (symbol: SV). [Diagram 5] FIG. 5 is a binarized image of the explanatory diagram (photograph) according to Example 1 shown in FIG. 4, in which black areas indicate voids and white areas indicate carbon materials (particles). [Figure 6]6 is an explanatory diagram (photograph) showing the structure (voids, aggregates) confirmed by SEM observation of the carbon material for catalyst carriers of Comparative Example 1 described later. The area surrounded by a white solid line in the figure shows an example of clumped carbon (symbol: C), and the area surrounded by a white dashed line shows an example of large voids (symbol: LV) formed between the clumped carbon. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The carbon material for a catalyst support of a polymer electrolyte fuel cell and the method for producing the same according to the present invention will be described in detail below. The carbon material for a catalyst support of a polymer electrolyte fuel cell of the present invention is a porous carbon material having a three-dimensionally branched dendritic structure and simultaneously satisfying the following (1) and (2). (1) In particle size distribution measurement using a laser diffraction / scattering particle size analyzer, the cumulative distribution [%] of particles with a particle diameter of 1 μm or less based on volume diameter is DL, and the cumulative distribution [%] of particles with a particle diameter of more than 1 μm is DH, and the DL / DH ratio is 1.5 or more. (2) The mode diameter of the pores in the range of 20 nm to 200 nm in diameter measured by mercury porosimetry is 40 nm to 70 nm.
[0019] First, having a three-dimensional dendritic structure branched three-dimensionally has the same meaning as what the inventors have previously proposed, and indicates that the rod-shaped or ring-shaped bodies are composed of dendritic carbon nanostructures having a three-dimensional dendritic structure branched three-dimensionally, as shown in Figure 4, etc.
[0020] Next, we will explain (1). In the carbon material for catalyst carrier of the present invention, the activation and crushing processes described below are performed to remove as much as possible the lump carbon that is relatively coarse, has many voids, and is light, which could not be removed by the classification process performed in the past, and therefore it is found that the particle size distribution is different from that of the past, and specifically, it is found that the lump carbon that was wanted to be removed is mostly in the range of 1 μm or more in size, and since it is required that the particle diameter of the carbon material for catalyst carrier is about 1 μm at most when used in a catalyst layer as described above, it is found that the proportion of the particle size of 1 μm will be small, and there is a good correlation with the power generation performance (large current characteristics) and durability described below. Then, for such characteristics, it was newly found that the particle size distribution of the obtained carbon material for catalyst carrier was measured, and the ratio DL / DH of the cumulative distribution (%) of particles with a particle diameter of 1 μm or less based on the volume diameter (hereinafter referred to as DL) to the cumulative distribution (%) of particles with a particle diameter of more than 1 μm (hereinafter referred to as DH) is used as an index. As for the specific measurement method, the frequency distribution and cumulative distribution shown in Figures 1 and 2 are used, and the cumulative (area) of the frequency distribution up to 1 μm in particle diameter is DL, and the cumulative (area) of the frequency distribution of particle diameters of 1 μm or more is DH, and the cumulative (area) of each region in the frequency distribution is expressed as a cumulative distribution. Here, the reason why DL is expressed as a ratio to DH is to understand the packing state of particles when the catalyst layer is formed, and the reason why DH, which is the target of exclusion, is included in the denominator is to recognize that there are sufficient fine particles compared to coarse particles. Note that this measurement is performed using a laser diffraction / scattering type particle size distribution meter (measuring device), because this method and measuring device are suitable for measuring particle size distributions of submicron to micron sizes with high accuracy. Furthermore, the reason why the "volume diameter standard" is adopted for the particle diameter is because it corresponds to the particle size distribution of the carrier particles present in the actual catalyst layer, and it can be assumed that it also corresponds to the fuel cell performance.
[0021] That is, the carbon material for catalyst carrier of the present invention is required to have DL / DH of 1.5 or more, preferably 2.5 or more, and more preferably 3.5 or more. When this DL / DH is less than 1.5, that is, when there is a relatively large amount of coarse aggregated carbon exceeding 1 μm, it is presumed that there are many carbon particles that are not exposed to the surface, that is, there are not enough voids for oxygen gas diffusion or water discharge, so when such a carbon material is used in the catalyst layer, there is a risk that the efficiency of catalyst utilization will be low, and there is a concern that the power generation performance of the fuel cell will be inferior. Note that there is no particular upper limit for the DL / DH ratio, and the larger the value (i.e., the smaller the cumulative distribution DH of particles with a particle diameter exceeding 1 μm) is, the more preferable it is.
[0022] Next, we will explain (2). As described above, in the carbon material for catalyst carriers of the present invention, the clumped carbon that should be removed is removed as much as possible, so that the macropores in particular have an optimal size, that is, the size is sufficient for the diffusion of oxygen gas and the discharge of generated water, and the catalyst density must be maintained. Regarding such characteristics, it has been newly discovered that the size of the macropores in the obtained carbon material for catalyst carriers is indexed by the position of the mode diameter in the diameter range of 20 nm to 200 nm in the pore distribution measured by the mercury porosimetry method. Here, the pore distribution measured is a log differential pore volume distribution, and the reason for using the mercury porosimetry method as the measurement method is that it is a suitable method for accurately measuring the material voids of the macropore size. In addition, the diameter range of 20 nm to 200 nm indicates the voids between branches and particles, and is suitable because the mode diameter (most frequent diameter) of the voids indicates the most frequent size of the path (void) for oxygen gas diffusion, etc., connecting the carbon particle surface and the outside of the catalyst layer.
[0023] That is, the carbon material for catalyst carrier of the present invention must have a mode diameter (peak position) in the range of 40 nm to 70 nm, preferably 45 nm to 65 nm, and more preferably 45 nm to 55 nm. If the mode diameter is less than 40 nm, it is presumed that the activation treatment or crushing described below is excessive and a healthy branch structure is not preserved, and therefore, when such a carbon material is used in a catalyst layer, there is a risk of a decrease in oxygen gas diffusion and a decrease in the mechanical strength of the catalyst layer. On the other hand, when the mode diameter is larger than 70 nm, it is presumed that there will be more voids than necessary for oxygen gas diffusion, and therefore, when such a carbon material is used in a catalyst layer, there is a risk of a decrease in the efficiency of catalyst utilization, and there is a concern that the power generation performance of a fuel cell will be deteriorated.
[0024] Furthermore, as described above, the carbon material for a catalyst support of the present invention has an integrated pore volume V of pores with diameters of 5 to 20 nm, which is determined by analysis of a nitrogen gas adsorption isotherm using the Dollimore-Heal method. 5-20 The V is preferably 0.17 to 0.50 mL / g, more preferably 0.17 to 0.40 mL / g, and further preferably 0.20 to 0.30 mL / g. 5-20 When measuring the nitrogen gas adsorption isotherm of the fuel cell catalyst layer, most of the nitrogen gas disappears, so it is speculated that V is used to adsorb ionomer resin (proton conductive resin). 5-20 It has been found that the adsorption amount of the ionomer resin is optimal when V is in the above range. 5-20 When V is less than 0.17 mL / g, it is considered that the carbon surface is covered with carbon with low aromaticity or the carbon particles are aggregated, which is undesirable in terms of catalyst utilization efficiency. 5-20 If the amount of ionomer resin exceeds 0.50 mL / g, an amount of ionomer resin greater than that required for the catalytic reaction will be attached to the carbon surface, and the ratio of ionomer resin in the catalyst will be high, that is, the ionomer resin will become thick on the carbon surface, which may make it difficult for oxygen gas to enter the carbon particles.
[0025] In addition, with respect to the carbon material for a catalyst support of the present invention, from the viewpoint of gas diffusion inside the micropores formed in the catalyst layer, the nitrogen gas adsorption amount V adsorbed at a relative pressure of 0.95 to 0.99 in the nitrogen gas adsorption isotherm is macro The amount of nitrogen gas adsorbed V in the range of the relative pressure from 0.95 to 0.99 is preferably 500 to 1600 cc (STP) / g, and more preferably 700 to 1200 cc (STP) / g. macro indicates the size of the macropores formed by the gaps between primary particles, and when this value is within the above range, the three-dimensional dendritic structure of the carbon material is highly developed. By developing a three-dimensional dendritic structure, it is possible to make the raw material gas (H 2 , O 2 ) The low supply and production of H 2 This makes it possible to avoid situations that arise due to poor discharge of O (such as situations in which the cell reaction is inhibited). In other words, this is preferable because it makes it possible to form a fuel cell with good large current characteristics.
[0026] In addition, as described above, the carbon material for a catalyst support of the present invention has a BET specific surface area of 400 to 1500 m as determined by BET analysis of the nitrogen gas adsorption isotherm. 2 / g, more preferably 500m 2 / g or more 1400m 2 When the BET specific surface area is in this range, the catalytic metal particles of several nm are supported in a well-dispersed state, that is, in a state in which the distance between the catalytic metal particles is maintained at a certain value or more and the particles can exist independently, which is preferable.
[0027] Furthermore, in order to enhance the crystallinity of the carbon material for a catalyst support of the present invention and thereby improve durability in a fuel cell use environment, the carbon material is preferably selected from the group consisting of a carbonaceous material having a crystallinity of 1550 to 1650 cm in a Raman spectrum. -1 The half-width ΔG of the G-band detected in the range of 50-70 cm -1 It is preferable that the length is 50 to 65 cm. -1This ΔG represents the extent of the carbon network plane of the carbon material, and ΔG is 50 cm -1 If it is less than 70cm, the carbon mesh surface spreads too much, the number of edges of the carbon mesh surface forming the pore wall decreases, and the support property of the catalytic metal fine particles on the pore wall tends to decrease. -1 If the thickness exceeds this value, the carbon net surface becomes narrow and the number of edges of the carbon net surface that are susceptible to oxidative wear increases, so durability tends to decrease.
[0028] In the method for producing such a carbon material for a catalyst carrier of the present invention, it is necessary to remove the above-mentioned clumped carbon contained in the carbon material intermediate obtained by heat treatment in a vacuum or in an inert gas atmosphere after removing silver from a composite material containing silver and carbon obtained by decomposition of silver acetylide, and according to detailed studies by the inventors of the present application, it has been found that for this purpose, it is effective to carry out pulverization (first and second steps) and contact with carbon dioxide (activation) in the following procedure. The procedure will be described below.
[0029] <First grinding process> In order to reduce the amount of aggregated particles (lump carbon) present in the carbon material intermediate obtained through the heat treatment and to make the particle size uniform, the heat-treated carbon material intermediate can be pulverized to reduce the particle size. The pulverization method in this first pulverization step may be either dry pulverization or wet pulverization, and these known methods can be used, but dry pulverization using a mortar, jet mill pulverization, roll mill pulverization, or the like is preferred because it can suppress the inclusion of foreign matter. From the viewpoint of increasing the efficiency of the activation treatment step described below, this first pulverization is preferably performed to reduce the amount of lump carbon as much as possible, specifically, with the aforementioned DL / DH=1 or more as an index.
[0030] <Contact with carbon dioxide (activation) process> The carbon material intermediate whose particle size has been reduced by the first pulverization step is heated in a carbon dioxide atmosphere for a predetermined time to obtain an activated porous carbon material. Here, the carbon dioxide atmosphere may contain a portion of an inert gas for reaction time control or the like, but is preferably an atmosphere of carbon dioxide gas other than unavoidable trace components, and is most preferably an atmosphere of only carbon dioxide (100 vol%). That is, such a step can consume the fragile carbon portion containing a large amount of non-aromatic components that remains in the carbon material intermediate. Such fragile carbon portions containing a large amount of non-aromatic components are contained in large amounts on the surface including the bonding portion between particles, and activation by heating in a carbon dioxide atmosphere can reduce the mechanical strength of the portion and the bonding strength between particles. The heating temperature in such a step is preferably 900 to 1100°C in order to maintain the carbon skeleton and selectively react carbon with a large amount of non-aromaticity as much as possible. The treatment time at a heating temperature in this range is preferably 0.2 to 3 hours, more preferably 0.5 to 2 hours.
[0031] <Second crushing process> The activated carbon material intermediate is then subjected to grinding again under a carbon dioxide atmosphere to obtain a porous carbon material for a catalyst support. This second grinding step may be either dry grinding or wet grinding, as in the first grinding step, and any of these known methods can be used, but grinding in a mortar, jet mill grinding, or dry grinding using a roll mill is preferred because it can prevent foreign matter from being mixed in. This second grinding is preferably performed using the particle size distribution measured by a laser diffraction / scattering method as an index, and grinding is preferably performed until the DL / DH is 1.5 or more.
[0032] It is presumed that the problematic clumped carbon is eliminated as much as possible through the above-mentioned pulverization (first and second steps) and contact with carbon dioxide (activation), and thus a carbon material for a catalyst support that satisfies the above-mentioned (1) and (2) specifications can be obtained. The carbon material intermediate to be subjected to the first pulverization step can be produced by blowing a predetermined amount of acetylene gas into a reaction solution consisting of an aqueous ammonia solution of silver nitrate to synthesize silver acetylide (silver acetylide production step), subjecting the obtained silver acetylide to an autolytic explosive reaction at a predetermined temperature (decomposition step), and then contacting the carbon material intermediate with a nitric acid solution to purify the carbon material intermediate and remove silver particles (washing step), and then heating the purified product at a predetermined temperature in a vacuum or in an inert gas atmosphere (heat treatment step). Each step will be described below.
[0033] (Silver acetylide production process) In the present invention, the silver acetylide production step is carried out by adjusting the mass ratio of acetylene gas and silver nitrate as described above, and the contact method of the acetylene gas can be, for example, passing acetylene gas through an aqueous silver nitrate solution, more specifically, blowing acetylene gas into the aqueous silver nitrate solution. In addition, ultrasonic waves can be irradiated to the aqueous silver nitrate solution when the aqueous silver nitrate solution is brought into contact with the acetylene gas. This has the effect of promoting the dissolution and dispersion of the acetylene gas in the aqueous silver nitrate solution. In this case, it is preferable to stir the aqueous silver nitrate solution when the aqueous silver nitrate solution is brought into contact with the acetylene gas. This increases the frequency of contact between the acetylene gas and the aqueous silver nitrate solution, resulting in efficient production of silver acetylide. Stirring can be performed using a general stirring blade or a stirring bar such as a magnetic stirrer. This allows silver acetylide to be obtained as a bulky precipitate of white crystals.
[0034] (decomposition process) Next, the obtained silver acetylide is decomposed by heating. By heating the silver acetylide, it explodes on a nanoscale and undergoes phase separation into silver and carbon, during which the silver forms nano-sized particles, or is gasified by the reaction heat and erupts onto the surface. Carbon has a highly aromatic structure because three acetylene-based compounds such as acetylene molecules tend to gather together to form a benzene ring. In addition, because silver forms nanoparticles, the carbon phase from which the silver has been removed becomes a porous structure.
[0035] Heating of silver acetylide can be carried out, for example, as follows. By heating the obtained silver acetylide precipitate under a reduced pressure atmosphere, for example, at 40°C to 100°C (this will be referred to as the "first heat treatment"), the solvent in the reaction solution remaining in the silver acetylide can be removed, the thermal energy of the explosion is prevented from being consumed as sensible heat for the phase transition of the solvent to the gas phase, and the decomposition of silver acetylide can be made more efficient. Note that silver acetylide does not decompose at this temperature.
[0036] Next, the silver acetylide from which the solvent has been removed is heated, for example, at 140°C to 400°C (this will be referred to as the "second heat treatment"). By heating the silver acetylide to such a relatively high temperature, the silver acetylide explodes and decomposes on a nanoscale, and the silver and carbon each form a nanostructure. This results in a composite material containing silver and carbon. The basic structure of the carbon phase of the composite material is mainly composed of several layers of graphene due to the formation of polycyclic aromatic compounds by the acetylene compound as described above. In addition, in the composite material, since silver forms nanoscale particles in the explosion process, the carbon material from which the silver particles have been removed has a large specific surface area and is highly porous.
[0037] (Cleaning process) A known method can be used to remove silver from a composite material containing silver and carbon. For example, a composite material containing silver and carbon can be immersed in hot nitric acid to dissolve the silver, thereby obtaining a purified carbon material from which the silver remaining on the surface and inside has been removed.
[0038] (Heat treatment process) The purified carbon material is heat-treated in a vacuum or in an inert gas atmosphere at a temperature of preferably 1400 to 2300°C, more preferably 1800 to 2250°C (this will be referred to as the "third heat treatment") to obtain a heat-treated carbon material intermediate. The heat treatment carried out in this step can develop crystals, and the crystallinity can be adjusted and controlled by the firing temperature. When the final catalyst support carbon material is used as a catalyst support for an electrode of a polymer electrolyte fuel cell, for example, it is exposed to a relatively high temperature, for example, about 80°C, a strong acidity of pH 1 or less, and a high potential of 1.3 V vs. SHE. In such an environment, the carbon in the porous catalyst support carbon material is easily oxidized and consumed. Therefore, when the porous catalyst support carbon material is used as a catalyst support, it is important to increase the crystallinity in this step.
[0039] As described above, if the temperature of the heat treatment step exceeds 2300°C, there is a risk that even highly aromatic carbon, which forms the skeleton of the carbon material for catalyst supports, will rapidly crystallize, which may make it difficult to disintegrate and grind the carbon material in the subsequent classification step, resulting in a reduced yield in the classification process, and therefore the temperature of the heat treatment step is preferably 2300°C or lower.The lower limit of the temperature of the heat treatment step is preferably 1400°C or higher, more preferably 1800°C or higher, from the viewpoint of improving the durability (the above-mentioned ΔG) of the obtained carbon material for catalyst supports. The heat treatment step can be carried out, for example, under a reduced pressure atmosphere or an inert gas atmosphere, but is not particularly limited thereto, and is preferably carried out under an inert gas atmosphere. The inert gas is, for example, but is not particularly limited thereto, and can be, for example, nitrogen, argon, or the like.
[0040] The carbon material for catalyst supports of the present invention is preferably composed of a dendritic carbon nanostructure having a three-dimensional dendritic structure in which rod-shaped or ring-shaped bodies are branched three-dimensionally as a catalyst support, and not only is it equivalent to or superior in BET specific surface area and durability to conventional dendritic carbon nanostructures of this type, but as described above, coarse clumped carbon is eliminated as much as possible, so that a catalyst layer prepared using this carbon material as a catalyst support has macropores formed that are suitable for diffusing reaction gases without resistance and for discharging water generated in the catalyst layer (produced water) without delay, and furthermore, there is little risk of a decrease in the utilization rate of the catalytic metal, and a solid polymer fuel cell can be obtained that has excellent power generation characteristics (high current characteristics) and durability as a fuel cell. EXAMPLES
[0041] Hereinafter, the carbon material for a catalyst support and the method for producing the same of the present invention will be specifically described based on examples and comparative examples. The carbon materials for catalyst supports prepared in the following Examples and Comparative Examples have the DL / DH ratios as defined in the above (1), the mode diameters (nm) as defined in the above (2), and the BET specific surface areas (m 2 / g), cumulative pore volume V of pores with diameters of 5 to 20 nm 5-20 , nitrogen gas adsorption amount V macro [cc(STP) / g], 1550-1650cm of Raman spectrum -1 The half-width of the G-band, ΔG (cm -1 ) were measured as follows. A part of the obtained carbon material for a catalyst support was observed with a scanning electron microscope (SEM).
[0042] <Laser diffraction / scattering particle size distribution measurement (DL / DH ratio measurement)> 10 mg of the carbon material for catalyst carrier prepared in each of the examples and comparative examples described below was weighed out in a sample bottle, 1 ml of 10% Liponox solution was added, and the material was dispersed by irradiating ultrasonic waves for 10 minutes in an ultrasonic cleaner. Next, 10% Liponox solution was added so that the transmittance was within a predetermined range, and the material was measured with a measuring device (LA-920 manufactured by Horiba, Ltd.). For the volume diameter-based particle size distribution obtained, with respect to the cumulative frequency obtained by integrating the frequency distribution, using 1 μm as the boundary, the cumulative distribution (%) of particles of 1 μm or less (cumulative area in the frequency distribution) DL and the cumulative distribution (%) of particles exceeding 1 μm (cumulative area in the frequency distribution) DH were determined respectively, and the DL / DH ratio was calculated from these values.
[0043] <Mode diameter in the pore diameter range of 20 nm to 200 nm by mercury porosimetry> For the carbon materials for catalyst carriers prepared in each of the examples and comparative examples described below, 30 mg of the material dried at a constant temperature of 120 °C for 4 hours was weighed, placed in a measurement cell, tapped, and the sample was loaded into the sample container of a measurement device (Autopore IV 9520 manufactured by Micromeritics). Mercury was injected under the conditions of an initial introduction pressure of 5 kPa and a maximum intrusion pressure of 400 MPa. Based on the obtained results, the pore distribution with a pore radius of approximately 0.0018 to 100 μm was determined. The pore diameter was calculated using Washburn's equation. Washburn's equation: PD = -4σcosθ Here, P: pressure, σ: surface tension of mercury, D: pore diameter, θ: contact angle between mercury and the sample. For the surface tension σ of mercury and the contact angle between mercury and the sample, values of σ = 480 dynes / cm and contact angle = 140 degrees were used respectively. Then, from the obtained log differential pore volume distribution [the increase in pore volume dV between each measurement point was divided by the logarithmic difference value d(logR) of the pore radius (R) and plotted with the average pore diameter of each section: dV / d(logR)], the most frequent diameter (peak) was determined as the mode diameter.
[0044] <BET specific surface area (m 2 / g), cumulative pore volume V of pore diameter 5 - 20 nm 5-20 and nitrogen gas adsorption amount V macro 〔cc(STP) / g〕measurement> Using the carbon materials for catalyst carriers prepared in each of the following Examples and Comparative Examples as samples, approximately 30 mg of each sample was weighed, vacuum-dried at 200 °C for 2 hours, and then the nitrogen gas adsorption isotherm was measured using an automatic specific surface area measuring device (AUTOSORB I-MP manufactured by Quantachrome Instruments Japan) with nitrogen gas as the adsorbate. BET analysis was performed in the range of relative pressure of 0.05 to 0.15 for the isotherm during adsorption to calculate the BET specific surface area. Also, the integrated pore volume V of pore diameters from 5 to 20 nm 5-20 was calculated by analyzing the same nitrogen gas adsorption isotherm using the Dollimore-Heal method (DH method) with the attached software. Furthermore, for the nitrogen gas adsorption amount V macro the value of V macro 〔cc(STP) / g〕was calculated as the difference between the adsorption amount [cc(STP) / g] at a relative pressure of 0.95 and the adsorption amount [cc(STP) / g] at a relative pressure of 0.99 for the same nitrogen gas adsorption isotherm.
[0045] <The full width at half maximum ΔG (cm -1 of the G-band detected in the range of 1550 to 1650 cm -1 )> Using the carbon materials for catalyst carriers prepared in each of the following Examples and Comparative Examples as samples, approximately 3 mg of each sample was weighed and then set in a laser Raman spectrophotometer (NRS-3100 type manufactured by JASCO Corporation). Measurement was carried out under the following conditions: excitation laser: 532 nm, laser power: 10 mW (sample irradiation power: 1.1 mW), microscopic configuration: Backscattering, slit: 100 μm × 100 μm, objective lens: ×100 magnification, spot diameter: 1 μm, exposure time: 30 sec, observation wavenumber: 2000 to 300 cm -1 , and the integrated number of times: 6 times. From the 6 spectra obtained, the full width at half maximum ΔG (cm -1 of the so-called graphite G-band appearing near 1580 cm -1 ) was determined, and the average value was taken as the measured value. The determination was made according to the following criteria.
[0046] <SEM Observation> In order to observe the state of the dendritic structure, the presence of clumped carbon, and the state of voids, the carbon materials for catalyst supports prepared in Example 1 and Comparative Example 1 described below were used as samples and observed using a high-resolution scanning electron microscope. The results are shown in Figures 4 to 6. As can be seen from Figures 4 and 5, in the carbon material for catalyst carriers of Example 1, for example, some small voids (symbol: SV) as surrounded by the white dashed line are observed, but large voids and structures resembling clumped carbon are hardly observed. On the other hand, as can be seen from FIG. 6, in the carbon material for a catalyst support of Comparative Example 1, clumps of carbon (symbol: C) were confirmed as shown in the area surrounded by the white solid line, and large voids (symbol: LV) formed between the clumps of carbon were confirmed as shown in the area surrounded by the white dashed line.
[0047] [Example 1] (1) Silver acetylide production process 46 g of silver nitrate was dissolved in 200 g of 25% by mass aqueous ammonia, and 2 L of water was added. Dry nitrogen was then blown in to remove residual oxygen. The solution was then stirred and immersed in an ultrasonic vibrator to vibrate it, while acetylene gas was blown in at a flow rate of 100 mL / min for 25 minutes. This caused silver acetylide solids to precipitate in the solution. The resulting precipitate was then filtered through a membrane filter, and during filtration, the precipitate was washed with methanol, and a small amount of methanol was added to impregnate the precipitate with methanol.
[0048] (2) Decomposition process About 0.5 g of the silver acetylide of each of the Examples and Comparative Examples obtained in the silver acetylide production process described above, while still impregnated with methanol, was placed in a stainless steel cylindrical container having a diameter of 5 cm, and this was placed in a vacuum dryer and vacuum dried at 30 to 40°C for 1 hour to prepare a silver particle-encapsulated intermediate derived from the silver acetylide (first heat treatment). Next, the silver particle-encapsulated intermediate obtained in the first heat treatment step at 30-40°C immediately after vacuum drying was rapidly heated to 160-200°C without being removed from the vacuum heating electric furnace, and heated for 20 minutes (second heat treatment). During this process, a nanoscale explosion reaction occurred in the container, the encapsulated silver was ejected, and a silver-encapsulated nanostructure with numerous ejection holes formed on the surface and inside was obtained as a composite material containing silver and carbon.
[0049] (3) Cleaning process 10 g of the composite material of silver and carbon obtained by the second heat treatment was immersed in 200 mL of a nitric acid solution with a concentration of 30% by mass, and washed at 90° C. for 2 hours to remove the remaining silver particles. Next, the nitric acid was removed from the carbon material after the washing using a centrifuge, and further, in order to sufficiently remove the remaining nitric acid, the carbon material after the centrifugation was dispersed again in pure water, which was then centrifuged again to separate the solid from the liquid. By performing such a water washing operation twice, a purified carbon material was obtained from which the nitric acid had been removed. The purified carbon material was dried by treating it at 140°C for 2 hours in an air atmosphere to remove moisture, and then heat-treated at 1100°C for 2 hours in an argon flow to obtain a porous carbon material.
[0050] (4) Heat treatment step (third heat treatment) The porous carbon material obtained through the washing treatment step (3) was further heated to 2000° C. at a rate of 15° C. / min under a flow of argon. After the predetermined temperature was reached, the temperature was maintained for 2 hours for heat treatment, and a carbon material intermediate was obtained.
[0051] (5) First crushing process The carbon material intermediate obtained in (4) above was subjected to crushing and classification simultaneously using an airflow crusher and classifier SJ-100GMP manufactured by Nisshin Engineering Inc. under conditions of a crushing pressure of 0.8 MPa and a powder insertion rate of 100 g / hr.
[0052] (6) Carbon dioxide contact (activation) step A few grams of the first crushed product obtained in (5) was placed in an alumina boat and placed inside a tubular electric furnace, and the atmosphere inside the tubular electric furnace was replaced with carbon dioxide gas of 100% by volume. Heat treatment was performed at a temperature of 1050°C for 0.5 hours while flowing carbon dioxide gas.
[0053] (7) Second crushing process The activated product of (6) above was pulverized and classified in the same manner as (5) above.
[0054] The carbon material for a catalyst support of Example 1 prepared as described above was evaluated by the above-mentioned method. The results are shown in Table 1.
[0055] [Examples 2 to 3] Except for changing the time of the activation treatment with carbon dioxide to 1 hour or 2 hours, each carbon material for a catalyst support was prepared in the same manner as in Example 1, and evaluated in the same manner. The results are shown in Table 1.
[0056] [Examples 4 to 5] Except for changing the temperature of the heat treatment step in obtaining the carbon material intermediate to 2100°C or 2250°C, and changing the time of the activation treatment with carbon dioxide to 1 hour, the respective carbon materials for catalyst supports were prepared in the same manner as in Example 1, and evaluated in the same manner. The results are shown in Table 1.
[0057] [Examples 6 to 7] Except for changing the temperature of the heat treatment step in obtaining the carbon material intermediate to 1900° C. or 1800° C., the respective carbon materials for catalyst supports were prepared in the same manner as in Example 1, and evaluated in the same manner. The results are shown in Table 1.
[0058] [Comparative Example 1] Except for not carrying out the contact (activation) step with carbon dioxide and not carrying out the second pulverization step, carbon materials for catalyst supports were prepared in the same manner as in Example 1, and were evaluated in the same manner. The results are shown in Table 1.
[0059] [Comparative Example 2] Except for not carrying out the second pulverization step, carbon materials for catalyst supports were prepared in the same manner as in Example 1, and evaluated in the same manner. The results are shown in Table 1.
[0060] [Comparative Examples 3 to 4] Except for changing the time of the contact (activation) step with carbon dioxide to 1 hour or 2 hours, and not carrying out the second crushing step, the carbon materials for catalyst supports were prepared in the same manner as in Example 1, and evaluated in the same manner. The results are shown in Table 1.
[0061] [Comparative Example 5] Except for changing the time of the contact (activation) step with carbon dioxide to 5 hours, carbon materials for catalyst supports were prepared in the same manner as in Example 1, and evaluated in the same manner. The results are shown in Table 1.
[0062] [Comparative Example 6] Except for not carrying out the contact (activation) step with carbon dioxide, carbon materials for catalyst supports were prepared in the same manner as in Example 1, and evaluated in the same manner. The results are shown in Table 1.
[0063] [Comparative Example 7] Carbon materials for catalyst supports were prepared in the same manner as in Example 1, except that the first pulverization step, the contact (activation) step with carbon dioxide, and the second pulverization step were not performed, and they were evaluated in the same manner. The results are shown in Table 1.
[0064] [Examples 8 to 9] Except for changing the temperature of the heat treatment step in obtaining the carbon material intermediate to 2300°C or 1400°C and changing the time of the contact (activation) step with carbon dioxide to 1 hour, each catalyst support carbon material was prepared in the same manner as in Example 1 and evaluated in the same manner. The results are shown in Table 1.
[0065] [Comparative Example 8] Except for changing the temperature of the heat treatment step in obtaining the carbon material intermediate to 2400° C. and changing the time of the contact (activation) step with carbon dioxide to 1 hour, each catalyst support carbon material was prepared in the same manner as in Example 1 and evaluated in the same manner. The results are shown in Table 1.
[0066] <Preparation of catalyst, preparation of catalyst layer, fabrication of MEA, assembly of fuel cell, and evaluation of cell performance (power generation performance, durability)> Next, using each of the catalyst carrier carbon materials prepared as described above, a catalyst for a polymer electrolyte fuel cell carrying a catalyst metal was prepared as follows, and a catalyst layer ink liquid was prepared using the obtained catalyst, and then a catalyst layer was formed using this catalyst layer ink liquid, and a membrane electrode assembly (MEA) was fabricated using the formed catalyst layer, and this fabricated MEA was incorporated into a fuel cell, and a power generation test was performed using a fuel cell measuring device. The preparation of each component and cell evaluation by power generation test are described in detail below.
[0067] (1) Preparation of catalysts for polymer electrolyte fuel cells (platinum-supported carbon materials) Each of the carbon materials for catalyst carriers prepared above was dispersed in distilled water, formaldehyde was added to the dispersion, and the dispersion was set in a water bath set at 40°C. After the temperature of the dispersion reached 40°C, the same as the bath, the dinitrodiamine Pt complex nitric acid aqueous solution was slowly poured into the dispersion under stirring. After that, stirring was continued for about 2 hours, and then the solid obtained was filtered and washed. The solid thus obtained was vacuum dried at 90°C, pulverized in a mortar, and then heat-treated at 200°C for 1 hour in an argon atmosphere containing 5% by volume of hydrogen to produce a platinum catalyst particle-supported carbon material. The platinum loading amount of this platinum-supported carbon material was adjusted to 25% by mass with respect to the total mass of the carbon material for catalyst carriers and the platinum particles, and was confirmed by measuring it by inductively coupled plasma atomic emission spectrometry (ICP-AES).
[0068] (2) Preparation of the catalyst layer Using the platinum-supported carbon material (Pt catalyst) prepared as described above, and using a 5 mass % Nafion solution (DE2020CS manufactured by DuPont, registered trademark: Nafion) as the electrolyte resin, the Pt catalyst and Nafion were mixed under an Ar atmosphere in a ratio of 1.0 times the mass of the Nafion solid content to the mass of the platinum catalyst particle-supported carbon material, and after lightly stirring, the Pt catalyst was crushed by ultrasonic waves. Further, ethanol was added so that the total solid content concentration of the Pt catalyst and the electrolyte resin was adjusted to 1.0 mass %, and a catalyst layer ink liquid in which the Pt catalyst and the electrolyte resin were mixed was prepared.
[0069] Ethanol was further added to each catalyst layer ink liquid having a solid content concentration of 1.0% by mass prepared in this manner to prepare a catalyst layer ink liquid for spray application having a platinum concentration of 0.5% by mass, and the mass of platinum per unit area of the catalyst layer (hereinafter referred to as "platinum coverage") was 0.2 mg / cm. 2 The spray conditions were adjusted so that the above catalyst layer ink for spray application was sprayed onto a Teflon (registered trademark) sheet, and then drying treatment was carried out in argon at 120° C. for 60 minutes to prepare a catalyst layer.
[0070] (3) Fabrication of MEA Using the catalyst layer prepared as above, an MEA (membrane electrode assembly) was prepared by the following method. A square electrolyte membrane with sides of 6 cm was cut out from a Nafion membrane (NR211 manufactured by Dupont). The anode and cathode catalyst layers coated on Teflon (registered trademark) sheets were cut into squares with sides of 2.5 cm using a cutter knife. The electrolyte membrane was sandwiched between the anode and cathode catalyst layers cut out in this manner so that the catalyst layers were in contact with each other, sandwiching the center of the electrolyte membrane, and the electrolyte membrane was then sandwiched between the anode and cathode catalyst layers so that the catalyst layers were in contact with each other, and the electrolyte membrane was then sandwiched between the anode and cathode catalyst layers cut out in this manner. The electrolyte membrane was then sandwiched between the anode and cathode catalyst layers, and the anode and cathode catalyst layers were then sandwiched between the cathode and the cathode catalyst layers, 2 After cooling to room temperature, the Teflon (registered trademark) sheets were carefully peeled off from both the anode and cathode to prepare a catalyst layer-electrolyte membrane assembly in which the anode and cathode catalyst layers were fixed to the electrolyte membrane.
[0071] Next, a pair of square carbon papers with sides of 2.5 cm were cut out from carbon paper (39BC manufactured by SGL Carbon Co., Ltd.) to form a gas diffusion layer. The catalyst layer-electrolyte membrane assembly was sandwiched between these carbon papers so that the anode and cathode catalyst layers were aligned with each other without any misalignment, and the resulting mixture was heated at 120°C and 50 kg / cm 2 The MEA was prepared by pressing for 10 minutes at RT. The basis weight of each component of the catalytic metal component, carbon material, and electrolyte material in each of the produced MEAs was calculated from the mass of the catalyst layer fixed to the Nafion membrane (electrolyte membrane) obtained from the difference between the mass of the Teflon (registered trademark) sheet with the catalyst layer before pressing and the mass of the Teflon (registered trademark) sheet peeled off after pressing, and was then calculated from the mass ratio of the composition of the catalyst layer.
[0072] (4) Assembly of fuel cells and evaluation of fuel cell power generation performance The MEAs produced using the carbon materials for catalyst carriers according to the respective Examples and Comparative Examples were assembled into cells, which were then set in a fuel cell measuring device, and the performance of the fuel cells was evaluated according to the following procedure. Air was supplied as an oxidizing gas to the cathode side, and pure hydrogen was supplied as a reactant gas to the anode side. The pressure was adjusted by a back pressure valve installed downstream of the cell so that the utilization rates were 40% and 70%, respectively, and the back pressure was 0.05 MPa. The cell temperature was set to 80°C, and the air and pure hydrogen supplied to the fuel cell were humidified by passing them through distilled water kept at 65°C in a humidifier (i.e., bubbling). This set the relative humidity of the anode and cathode to about 100%.
[0073] Under these conditions, the reactant gas was supplied to the cell, and the load was gradually increased until the current density reached 1000 mA / cm 2 The cell terminal voltage at this point was recorded as the output voltage, and the performance of the fuel cell was evaluated using the following criteria of pass rank A or B and fail rank C. The results are shown in Table 1. [Passing rank] A: 1200mA / cm 2The output voltage is 0.65V or more. B: 1200mA / cm 2 The output voltage is 0.60V or more. [Failed rank] C: Does not meet the passing grade B.
[0074] (5) Evaluation of durability In the above cell, the anode was left as it was, and argon gas was passed through the cathode under the same humidification conditions as above, while the cell voltage was set to 1.0 V and held for 4 seconds, and then set to 1.3 V and held for 4 seconds (repeated rectangular wave voltage fluctuation operation), which constituted one cycle. After 250 cycles of this rectangular wave voltage fluctuation operation, durability was investigated in the same manner as in the evaluation of the large current characteristics described above, and evaluation was performed according to the following criteria of pass ranks A and B and fail rank C. The results are shown in Table 1. [Passing rank] A: 1200mA / cm 2 The output voltage is 0.65V or more. B: 1200mA / cm 2 The output voltage is 0.60V or more. [Failed rank] C: Does not meet the passing grade B.
[0075] [Table 1]
Claims
1. A carbon material for a catalyst support is used as a catalyst support for a polymer electrolyte fuel cell, and has a three-dimensionally branched dendritic structure, the carbon material for a catalyst support being characterized in that it simultaneously satisfies the following (1), (2), and (3): (1) In particle size distribution measurement using a laser diffraction / scattering particle size distribution analyzer, the cumulative distribution [%] of particles with a particle diameter of 1 μm or less based on the volume diameter standard is DL, and the cumulative distribution [%] of particles with a particle diameter of more than 1 μm is DH, and the DL / DH ratio is 1.5 or more. (2) The mode diameter in the range of pore diameters of 20 nm to 200 nm measured by mercury porosimetry is 40 nm to 70 nm. (3) The BET specific surface area, as determined by BET analysis of a nitrogen gas adsorption isotherm, is 370 to 1650 m 2 / g.
2. The cumulative pore volume V of pores with diameters of 5 to 20 nm obtained by analyzing the nitrogen gas adsorption isotherm using the Dollimore-Heal method 5-20 The carbon material for a catalyst support according to claim 1, characterized in that the molecular weight is 0.17 to 0.50 mL / g.
3. In the nitrogen gas adsorption isotherm, the amount of nitrogen gas adsorbed at a relative pressure of 0.95 to 0.99 V macro 3. The carbon material for a catalyst support according to claim 1, wherein the molecular weight is 500 to 1600 cc (STP) / g.
4. The BET specific surface area determined by BET analysis of the nitrogen gas adsorption isotherm is 400 to 1500 m 2 4. The carbon material for a catalyst support according to claim 1, wherein the molecular weight of the carbon material is 1000 or more.
5. Raman spectroscopy at 1550-1650 cm -1 The half-width ΔG of the G-band detected in the range of 50 to 70 cm -1 5. The carbon material for a catalyst support according to claim 1, wherein
6. The cumulative pore volume V of pores with diameters of 5 to 20 nm determined by analysis of nitrogen gas adsorption isotherms using the Dollimore-Heal method 5-20 The carbon material for a catalyst support according to any one of claims 2 to 5, characterized in that the molecular weight distribution of the carbon material is 0.17 to 0.40 mL / g.
7. A method for producing a carbon material for a catalyst support of a polymer electrolyte fuel cell, comprising the steps of: The method includes a step of removing silver from a composite material containing silver and carbon obtained by decomposing silver acetylide, and then performing a heat treatment at a temperature of 1400° C. or more and 2300° C. or less in a vacuum or in an inert gas atmosphere to obtain a carbon material intermediate, Next, the method for producing a carbon material for a catalyst support comprises a first crushing step of crushing the carbon material intermediate, an activation step of bringing the crushed carbon material into contact with carbon dioxide to activate it, and a second crushing step of crushing the activated carbon material, wherein the activation step lasts for 0.2 to 3 hours.
Citation Information
Patent Citations
Silver acetylide and method of producing the same
JP2018172230A
Carbon material for catalyst carrier of solid polymer fuel cell and manufacturing method thereof, and catalyst carrier for solid polymer fuel cell arranged by use of carbon material for catalyst carrier
JP2018174078A
Carbon material for use as catalyst carrier
WO2014129597A1
Supporting carbon material for solid polymer fuel cell, metal-catalyst-particle-supporting carbon material, and method for manufacturing said materials
WO2015088025A1
Supporting carbon material for solid polymer fuel cell and catalyst metal particle-supporting carbon material
WO2015141810A1